Bilinear modelling and bilinear PI control of directional drilling - Inyang, Isonguyo J.; Whidborne, James F.; Bayliss, Martin T. (IEEE, 2016)
This paper presents the design of an inclination- and azimuth-hold controllers and their subsequent stability and performance analysis for directional drilling tools as typically used in the oil industry. Using an input transformation developed in earlier work that partially linearizes and decouples the plant dynamics of the directional drilling tool, a bilinear model of the directional drilling tool is developed and is used as the basis for Bilinear PI controller design. Results for a transient simulation of the proposed BPI controller are presented and compared with that of the PI controller of the earlier work. It is presented that BPI controller gives more consistent responses over a broader operating range compared to the PI controller. In addition, the effect of time delay on the feedback measurements with respect to the stability and performance is investigated in the simulations.
Keywords: Azimuth; Attitude control; Mathematical model; Transient analysis; Feedback loop; Control systems; Computational modelling